The 100th day of school eaudiobook - O'Connor, Jane (I Can Read, Level 1: Fancy Nancy, 2010)
All the students in Ms. Glass's class are doing a project for the 100th Day of School. Nancy finds a way to combine her project with a touching tribute to her goldfish, Goldy.